Serum metabolic patterns reveal the diagnostic and prognostic role of alanine abnormality in ocular adnexal lymphoma - Yida Huang; Huimin Lin; Jiahao Shi; Yifan Chen; Qi Sang; Ruimin Wang; Wanshan Liu; Jiao Wu; Yanyan Li; Xiaoyu Xu; Chunmeng Ding; Shouzhi Yang; et al. (Proceedings of the National Academy of Sciences, 2025)
Ocular adnexal lymphoma (OAL) is the most common orbital malignancy in adults. Advanced tools for precise diagnosis and prognosis of OAL are in demand. Here, the nanoparticle-enhanced laser desorption/ionization mass spectrometry was applied for the construction of OAL-associated serum metabolic patterns (SMPs) from 239 participants (104 OAL and 135 non-OAL). Through machine learning, the diagnostic performance with an area-under-the-curve (AUC) of 0.901 was achieved for OAL based on SMPs. Furthermore, a diagnostic metabolic panel was constructed with an AUC of 0.875. Moreover, a prognosis scoring system was built and its desirable prediction efficacy for progression-free survival of OAL was confirmed ( P < 0.05). Specifically, the decreased serum alanine level was found to play both vital roles in the diagnosis and prognosis of OAL, and we demonstrated that uptake of alanine promotes glycolysis and cell growth in lymphoma cells. Our study highlights the value of the serum metabolite biomarkers in the clinical management of OAL.